Water balance - stream discharge from Tarfalajokk, Stream level & Discharge - Tarfala Research Station (Stockholm University, 2021)
Discharge calculations based on stream level measurements and a constantly validated stream discharge relation curve. For detailed information on calculations and installation read COMMENT in the header of the data set, which guides to related information document.
Tarfala Research Station (2021). Water balance - stream discharge from Tarfalajokk, Stream level & Discharge, 2017-05-25–2017-09-14 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/NJ1RzGs62ffH5D0xPxeV_MF1
Keywords: Tarfala Research Station; Discharge; Stream; Time instant; Time instant; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap